Inhibition of Cell Division Induced by External Guide Sequences (EGS Technology) Targeting ftsZ - Sala, Carol Davies (Public Library of Science, 2012)

(untitled)
EGS (external guide sequence) technology is a promising approach to designing new antibiotics. EGSs are short antisense oligoribonucleotides that induce RNase P-mediated cleavage of a target RNA by forming a precursor tRNA-like complex. The ftsZ mRNA secondary structure was modeled and EGSs complementary to two regions with high probability of being suitable targets were designed. In vitro reactions showed that EGSs targeting these regions bound ftsZ mRNA and elicited RNase P-mediated cleavage of ftsZ mRNA. A recombinant plasmid, pEGSb1, coding for an EGS that targets region “b” under the control of the T7 promoter was generated. Upon introduction of this plasmid into Escherichia coli BL21(DE3)(pLysS) the transformant strain formed filaments when expression of the EGS was induced. Concomitantly, E. coli harboring pEGSb1 showed a modest but significant inhibition of growth when synthesis of the EGSb1 was induced. Our results indicate that EGS technology could be a viable strategy to generate new antimicrobials targeting ftsZ.